Business Process Modeling for Sorghum Entrepreneurs Using Business Model Canvas - Noerhartati, Endang; Saurina, Nia (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Business models are required because of the features of market economies where there is consumer choice, transaction costs, heterogeneity amongst consumers and producers, and competition. Since 2009, Universitas Wijaya Kusuma Surabaya (UWKS) has been involved in the intensification of alternative food programs and substitution of imported food as well as encouraging sorghum commodity entrepreneurship. UWKS created the Unit Entrepreneurs Sorghum (UES), which aims to create new entrepreneurs in the sorghum sector, so that the development of sorghum as an alternative food can be maximized. Untill now there are 26 Units Entrepreneurship Sorghum (UES) have been formed). It is crucial for UES to understand the description of the running business model to determine the appropriate competitive strategy to be implemented. Thus, the study focuses on conducting research in the form of business model canvas implementation on the Unit Entrepreneur Sorghum in UWKS. This research used the observation, in- depth interview, and questionnaire to 26 UES. The study of literature review was also implemented in collecting the data and information to discover the phenomena and problem which required to be solved.The identification of business model of UES is conducted through mapping the nine building blocks of business model canvas: customer segments, value propositions, channels, customer relationships, revenue streams, key activities, key resources, key partnerships, and cost structure. The analysis shows that it requires the improvement in almost all nine blocks of business model canvas for sorghum entrepreneur. The business model improvement for sorghum entrepreneur focuses on the marketing activity. It should be prioritized in the digital marketing to increase the revenue streams of sorghum entrepreneur.